EXPLORING THE INTENTION AND RESISTANCE OF THE CUSTOMER IN ADOPTING THE TECHNOLOGY INNOVATION: A QUALITATIVE STUDY ON THE NFC-BASED MOBILE PAYMENT - Pitari, Diananda Fitri; Gayatri, Gita; Furinto, Asnan; Assauri, Sofjan (ASEAN Marketing Journal, 2021)
Manuscript type: Empirical Research Aims: To explore what do the potential customers of NFC-Based mobile payment perceive to be the key attributes of both the factors- intention and resistance- in determining the adoption of innovation? Design/methodology/approach: Qualitative Study using in-depth Interview Research Findings: Preliminary result suggests existence of three intention, which are: relative advantage, complexity and compatibility; as well as the six resistance factors: value barrier, usage barrier, tradition barrier, risk barrier, image barrier, resistance to change and satisfaction for status quo, - influencing the willingness to adopt the NFC Mobile payment. Theoretical Contribution/Originality: To enrich and confirm the adoption-innovation behavior, where the intention as well as retention on the adoption the new innovation is combined together in order to grab more comprehensive understanding on adoption new innovation. From the adoption resistance perspective, this research explores both active and passive innovation resistance to fully understand their influences on innovation resistance. Practitioner/Policy Implication: The findings in this research might be useful as a preliminary basis for confirming the factors that might boost or hinder the customers’ adoption innovation in the context of financial information technology product, especially the NFC-based mobile payment. Research limitation/Implications:As in any qualitative research, the generalization and applicability of this study is limited to the context of the NFC-based mobile payment. Further research might use the findings to test the intention and resistance factors of adoption innovation in the context of financial product. The framework can also be empirically tested with different consequence variables such as customer expectation to adopt new innovation (Venkatesh et al., 2008) using the descriptive research